ROAD TRANSPORT OF GOODS IN INDONESIA: INFRASTRUCTURE, REGULATORY AND BRIBERY COSTS - Brasukra G Sudjana (Universitas Trisakti, 2011)
Indonesia’s logistics costs have been identified as the weak link in the country’s price competitiveness. Part of this problem is attributed to the cost of domestic transportation. This article attempts to quantify the components of domestic transportation of goods overland, especially those due to infrastructure, regulatory barriers, and illegal charges. The study focuses on Sulawesi and covers six routes connecting major cities on the island, as well as three other comparator routes in Sumatra, Java, and West Nusa Tenggara. This report finds that while a big portion of the cost comes from Indonesia’s topography (and lack of infrastructural development to tackle these topography, such as the building of highways), some 10% of transportation cost is due to regulatory and illegal charges.